Impact of maternal hyperlipidic hypercholesterolaemic diet on male reproductive organs and testosterone concentration in rabbits. (3rd March 2014) - Dupont, C.; Ralliard-Rousseau, D.; Tarrade, A.; Faure, C.; Dahirel, M.; Sion, B.; Brugnon, F.; Levy, R.; Chavatte-Palmer, P.
Abstract : The concept of Developmental Origins of Health and Disease initially stemmed from the developmental programming of metabolic diseases. Reproductive functions and fertility in adulthood may also be programmed during foetal development. We studied the impact of dietary-induced maternal hyperlipidaemia and hypercholesterolaemia (HH), administered at 10 weeks of age and throughout the gestation and lactation, on male reproductive functions of rabbit offspring. Male rabbits born to HH dams and fed a control diet had significantly lighter testes and epididymes compared with rabbits born to control dams at adulthood. No significant changes in sperm concentration, sperm DNA integrity and sperm membrane composition were observed, but serum-free testosterone concentrations were decreased in HH males. This study confirms the importance of maternal metabolic status for the development of male reproductive organs.